Pengaruh Kurikulum Merdeka Terhadap Kemampuan Pemecahan Masalah Pada Siswa SMP Negeri 11 Kota Bima - Andriani, Vivi Andriani; Suswati, Lis; Yusiran, Yusiran (Gravity Edu : Jurnal Pembelajaran dan Pengajaran Fisika, 2024)
This research was motivated by the lack of students' ability to solve problems in using the independent curriculum, where in this curriculum students are required to be independent in learning. So that certain models are sought in learning to improve this. So researchers use models problem solving as one of the learning models that will be used in this research. In this research there are 4 (four) indicators of problem solving, namely identifying problems, formulating problems, implementing strategies, verifying solutions. This research aims to determine the effect of the independent curriculum on the problem solving abilities of students at SMP Negeri 11 Bima City. This research design uses Quasi Experiment with one experimental class. The data collection technique uses essay test sheets, namely the initial test (pre-test) before being given treatment and the final test (post-test) after being given treatment. The data analysis technique used to test the hypothesis is the paired sample t-test technique, based on the results of the data analysis obtained it can be shown that tcount = 14.5775236 with a significance level = 0.05 so that t is obtainedtable = 14.88399. From the calculation results obtained tcount < ttable then it is concluded that Ha accepted